The pandemic health crisis and its implications for food and nutritional security in Latin America - Giordani,Rubia Carla Formighieri (2020)
Abstract The inequalities in health are directly linked to food and to the nutritional profile; hunger and malnutrition, as well as overweight and obesity, increase in proportion to poverty. In the current COVID-19 pandemic scenario, social isolation measures implemented in several countries to prevent the collapse of health systems impose new rhythms on people’s lives and their daily routines, implying a reorganization of their vital structure and the necessary activities for its maintenance and reproduction. The restriction of circulation with the requirement to prepare food inside the home imposes food planning with options with some degree of industrial processing. In the diet of isolation, among the likely changes in food consumption models, there will certainly be an increase in ultraprocessed foods, mainly because containment measures have altered the dynamics of circulation and local trade of fresh products.